2022
DOI: 10.1186/s12872-022-02900-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of interrupting dual antiplatelet therapy one month following percutaneous coronary intervention: a meta-analysis of randomized controlled trials

Abstract: Very short duration of dual antiplatelet therapy (DAPT) following percutaneous coronary intervention (PCI) has recently attracted a lot of attention with the introduction of newer generations stents. This is appealing, especially in patients at high bleeding risk. However, none of the trials were powered for the individual ischemic and bleeding endpoints. All randomised controlled trials (RCTs) investigating one-month versus routine duration of DAPT in patients undergoing PCI and reporting outcomes from the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…The STOPDAPT-2 (Short and Optimal Duration of Dual Antiplatelet Therapy After Everolimus-Eluting Cobalt-Chromium Stent-2) trial found that in PCI patients, one month of DAPT followed by clopidogrel monotherapy had a much lower rate of cardiovascular and bleeding events than 12 months of DAPT with aspirin and clopidogrel. Additionally, a recent meta-analysis of these studies found no significant differences between the rates of all-cause mortality, stroke, MI, and ST during the follow-up period of 1 month to 1 year when comparing one-month DAPT to routine DAPT in patients undergoing PCI [4,[11][12][13].…”
Section: Premature Cessation Of Dual Antiplatelet Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The STOPDAPT-2 (Short and Optimal Duration of Dual Antiplatelet Therapy After Everolimus-Eluting Cobalt-Chromium Stent-2) trial found that in PCI patients, one month of DAPT followed by clopidogrel monotherapy had a much lower rate of cardiovascular and bleeding events than 12 months of DAPT with aspirin and clopidogrel. Additionally, a recent meta-analysis of these studies found no significant differences between the rates of all-cause mortality, stroke, MI, and ST during the follow-up period of 1 month to 1 year when comparing one-month DAPT to routine DAPT in patients undergoing PCI [4,[11][12][13].…”
Section: Premature Cessation Of Dual Antiplatelet Therapymentioning
confidence: 99%
“…Shorter DAPT durations after ACS were associated with higher rates of ST and myocardial infarction [8,9]; • No differences between short-duration and standard-duration DAPT in terms of effectiveness results, with short-term DAPT being an option for patients at high risk of bleeding [3]; • A single month of DAPT was non-inferior to the long-term DAPT in terms of the risk of MACE [4,11,13]; • DAPT withdrawal was not linked to poorer 1-year TLF following COMBO stenting [17]; • Younger patients had a higher cardiovascular risk associated with disruption, whereas those over 75 did not [18]; •…”
mentioning
confidence: 99%
“…The latest ESC guidelines [ 24 ] recommend six months of DAPT, whereas the ACC/AHA guidelines [ 25 ] recommend three to six months of DAPT following elective PCI (EXCELLENT [ 26 ], SECURITY [ 27 ] AND ISAR-SAFE [ 28 ] trials). The benefit beyond this period is minimal at the expense of an increased risk of major bleeding [ 29 , 30 ] and non-cardiovascular death [ 31 , 32 , 33 ], as shown in several meta-analyses. A shorter duration of dual antiplatelet medication (between one and three months) can be considered in patients with high bleeding risk (GLOBAL LEADERS [ 34 ], MASTER DAPT [ 35 ], STOPDAPT 2 [ 36 ] and one-month DAPT [ 37 ] trials).…”
Section: Antiplatelet Therapy Following Elective Percutaneous Coronar...mentioning
confidence: 99%
“…Assim como Zhong e colaboradores apontaram que a redução da taxa de sangramento maior a partir do uso de TDAP abreviada esteve em uma faixa entre (43%-46%), os benefícios dessa estratégia também foram sustentados pelos estudos de Parfrey, et al, 2022;Rout, et al, 2023;Benenati, et al, 2021;Landi, et al, 2023).…”
Section: Tdap Ultra-rápida (≤ 3 Meses) Comparada a Outras Modalidadesunclassified